Development of a two-step protocol for culture expansion of human annulus fibrosus cells with TGF-β1 and FGF-2. Issue 1 (December 2016) - Chou, Po-Hsin; Wang, Shih-Tien; Ma, Hsiao-Li; Liu, Chien-Lin; Chang, Ming-Chau; Lee, Oscar
Abstract Background Different biologic approaches to treat disc regeneration, including growth factors (GFs) application, are currently under investigation. Human annulus fibrosus (hAF) repair or regeneration is one of the key elements for maintenance and restoration of nucleus pulposus function. However, so far there is no effective treatment for this purpose. The aim of the present study was to investigate the response of hAF cells to different combinations of GFs, and develop a protocol for efficient culture expansion. Methods hAF cells were harvested from degenerated disc tissues during surgical intervertebral disc removal, and hAF cells were expanded in a monolayer. The experiments were categorized based on different protocols with transforming growth factor (TGF-β1) and fibroblast growth factor (FGF-2) culture for 14 days: group 1 had no GFs (control group); group 2 received TGF-β1; group 3 received FGF-2; group 4 received both GFs; and group 5 (two-step) received both GFs for the first 10 days and TGF-β1 only for the next 4 days. Cell proliferation, collagen, and noncollagen extracellular matrix (ECM) production and genes expression were compared among these groups. Results At days 3, 7 and 10 of cultivation, groups 4 and 5 had significantly more cell numbers and faster cell proliferation rates than groups 1, 2, and 3. At 14 days of cultivation, significantly more cell numbers were observed in groups 3 and 4 than in group 5. The group 4 had the most cell numbers and the fastest proliferation rate at 14 days of cultivation. After normalization for cell numbers, group 5 (two-step) produced the most collagen and noncollagen ECM at 10 and 14 days of cultivation among the five groups. In group 5, ECM gene expression was significantly upregulated. High expression of matrix metalloproteinase-1 was upregulated with FGF-2 on the different days as compared to the other groups. Annulus fibrosus cell phenotypes were only marginally retained under the different protocols based on quantitative polymerase chain reaction results. Conclusion Taken together, the two-step protocol was the most efficient among these different protocols with the most abundant ECM production after normalization for cell numbers for culture expansion of hAF cells. The protocol may be useful in further cell therapy and tissue engineering approaches for disc regeneration.